EFFICACY OF ALBENDAZOLE AGAINST PARAMPHISTOMUM SP. INFECTIONS IN BALI CATTLE IN BALI - Ni Komang Sri Ratih; I Wayan Sudira; I Made Dwinata (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Paramphistomosis, caused by the trematode Paramphistomum sp., is a prevalent parasitic disease affecting Bali cattle that leads to significant health issues and productivity losses. This study evaluated the anthelmintic efficacy of albendazole (10 mg/kg BW) against Paramphistomum sp. infections in Bali cattle through fecal egg count reduction. Using a one-group pretest-posttest design, we examined 20 naturally infected Bali cattle (aged 6 months-2 years) from three locations in Bali (Bangli Regency, Badung Regency, and Denpasar City). Fecal samples were collected on day 0 (pretreatment), day 7, and day 14 post-treatment and analyzed using the Whitlock sedimentation method. The Fecal Egg Count Reduction Test (FECRT) and Paired Sample T-test were employed for data analysis. Results demonstrated a statistically significant reduction (p<0.05) in egg counts post-treatment, with FECRT reaching 87.80% by day 14. These findings indicate that albendazole is effective against Paramphistomum sp. infections in Bali cattle, supporting its use in control programs.